Kontribusi Objek Wisata Pantai Sujono Terhadap Pendapatan Masyarakat Dan Pendapatan Asli Daerah (PAD), Di Desa Lalang, Kecamatan Medang Deras, Kabupaten Batu Bara - Sari, Lutfiah Nilam; Pinem, Mbina (Mahesa Research Center, 2023)
This study aims to determine: Physical conditions, visitor perceptions, the contribution of the Sujono Beach tourist attraction to community income and local revenue (PAD). This research was conducted in Lalang Village with a population as well as samples from a number of 35 families (Heads of Families), 1 government agency namely the Department of Youth, Sports and Tourism of Batu Bara Regency (Dispora), and 10 visitors (tourists). In this way, the total sample obtained is 46 samples by means of Total Sampling. Data collection techniques used in this study were observation, interviews, questionnaires, and documentation with qualitative descriptive analysis. The results of the research show that: (1) The physical condition consists of several types of pine trees; ketapang tree; Palm tree; Mango tree. (2) Tourist perceptions of tourist objects from all the facilities provided are classified as unfavorable/unsatisfied, in terms of accessibility conditions, physical conditions, cleanliness conditions and conditions in use at the Sujono Beach tourist attraction. (3) The contribution of the Sujono Beach tourist attraction to community income is 78.65%. This can be related to the 2019 Batu Bara Regency UMK (Rp. 3,191,570), so (78.65%) the community's needs have not met their daily needs and are below the UMK. (4) The contribution generated by Regional Original Revenue (PAD) can be seen from 2015 contributing 6.06% and is increasingly decreasing.